Performance Analysis of Optical Amplifiers in Optical Communication System - Sanghi, Aman (My University, 2007)
Information revolution implies that multimedia networks need high bandwidth real-time communication services. At present, optical fiber is the only transmission medium offering such large bandwidth with low loss communication links. With growing transmission rates, electronic regeneration becomes more and more expensive. Optical amplifiers are in general bit rate transparent and can amplify signals at different wavelength simultaneously. Optical amplifiers are mainly of two types i.e. Semiconductor optical amplifiers and Fiber amplifiers and further classified into traveling wave semiconductor optical amplifier, fabry-perot semiconductor optical amplifier, Erbium doped fiber amplifier, Raman & Brillouin fiber amplifiers. Optical wavelength converters are the key components for multi-wavelength optical transport networks and provide wavelength conversion in optical domain with out distortion of input signal. Wavelength converters increase the flexibility and capacity of networks for a fixed set of wavelength. The electro-optic converter is a straight forward solution for conversion, but electro-optic converter has limitations such as large power consumption and complexity. Wavelength conversions based on semiconductor optical amplifiers (SOAs) and semiconductor lasers have been focused on research interests during the last few years. Semiconductor optical amplifiers used in cross gain modulation mode (XGM), cross phase modulation (XGM) and four wave mixing (FWM) mode for wavelength conversions. It is reported earlier by some authors that all optical up conversion use cross gain modulation of the SOA with high conversion efficiency, but it requires a large input optical power to saturate the gain of the SOA. Extinction ratio degradation problem is also presented in the XGM scheme. In this thesis, the simulation results of cross phase wavelength conversion in semiconductor optical amplifiers have been presented. The cross gain modulation scheme shows extinction ratio degradation for conversion to longer wavelengths and this can be overcome using cross phase modulation in semiconductor optical amplifiers that are integrated into interferometric structures It is seen that the BER values is very high at low current but as we increase the bias current, BER value continuously falls. It is observed from the results that minimum BER value comes out around 10-40 at power 0.35 mW. It’s also evaluated from results that BER has minimum value around 10-40 at power 0.35 mW for 0.3 A value of bias current for up conversion. It is noticed from the results that minimum BER value comes out around 10-30 at power 0.3 mW. It is also evaluated from the results that minimum BER comes out around 10-100 at power 0.3 mW for down conversion. Furthermore in this thesis we studied about the optical amplifier for Dense Wavelength Division Multiplexing (DWDM). Erbium Doped Fiber Amplifier (EDFA) is used in the optical communications technology at the standard telecornmunication wavelength of I550 nm. We studied the simulation effects of gain value with pump power and wavelength of amplifier has been presented. The results of the various configurations for gain spectrum with pump power of the EDFA are enumerated. Variation in the noise figure with pump power and EDFA length is also depicted in this study. In order to observe the performance of gain compensation of EDFA, gain of EDFA verses pump power is studied for different lengths of EDFA. It is also seen that maximum gain value is 18.88 dB for pump power 3 mW and the minimum noise figure value comes out 0.0079 dB at pump power 3 mW.
Keywords: Optical Amplifiers; Raman Amplifiers; Brillouin Fiber Amplifier; Four-Wave Mixing